Long-term effects of zonisamide in adult patients with intellectual disability - Eck, Kattrinna; Rauch, Christophe; Kerling, Frank; Hamer, Hajo; Winterholler, Martin (Acta Neurologica Scandinavica, 2021)
Objective This study aimed to evaluate the tolerability and efficacy of zonisamide (ZNS) in adult patients with drug-resistant epilepsy and intellectual disability (ID) at our epilepsy centre.
CRIS-Team WoS Importer:2021-05-21